Cor Triatriatum: an uncommon congenital anomaly - the experience of a tertiary care center in a developing country - Abdul Khalek, Jad; El Rassi, Christophe; Abou Mansour, Maria; Sleem, Bshara; El Rassi, Issam; Bitar, Fadi; Arabi, Mariam (Frontiers in Cardiovascular Medicine, 2025)
BackgroundCor Triatriatum is a congenital anomaly characterized by the abnormal presence of a fibromuscular junction in one of the atria, as seen on echocardiography. This anomaly can lead to major hemodynamic problems and obstruction of blood flow. This study aims to explore the risk factors, diagnostic modalities, and surgical interventions used to tackle this congenital anomaly at a tertiary care center over an 18-year period.Materials and methodsMedical records of congenital heart disease patients at the Children's Heart Center at the American University of Beirut Medical Center between 2006 and 2024 were retrospectively reviewed. Data collection included demographic characteristics, clinical outcomes, hospitalization details, and surgical treatment. Ethical approval was obtained, and descriptive statistics were employed for data analysis using SAS 9.4.ResultsAt our center, 7 patients were diagnosed with Cor Triatriatum, with a median age of 5 months. 4 of the patients were female, 3 were males, and the median hospital stay was 7 days. All patients were diagnosed with Cor Triatriatum Sinister, and respiratory symptoms were prevalent. Pulmonary vein abnormalities were observed in 4 ouf of 7 (57.1%) patients and atrial septal defects in 2 out of 7 patients (28.5%). Surgery resulted in successful membrane resection for all operated patients, with significant symptom improvement postoperatively.ConclusionCor Triatriatum is a rare congenital anomaly requiring early detection and diagnosis. Surgical intervention remains the mainstay of treatment, with favorable outcomes when performed promptly. Larger studies are recommended to optimize management strategies and improve long-term outcomes for affected patients.